Treatment of Recurrent Eczema Herpeticum in Pregnancy With Acyclovir - Richard A. Latta; David A. Baker (Hindawi Limited, 1996)
Background: Eczema herpeticum is an uncommon manifestation of an infection with herpes simplex virus (HSV). The disease is primarily seen in patients with histories of atopic eczema. Eczema herpeticum may be a life-threatening illness, but the mortality is felt to be <10% with modern antiviral and antibacterial agents. The use of acyclovir for other viral infections secondary to herpesvirus in pregnancy has been well documented. The authors now present a case report of eczema herpeticum treated with acyclovir during pregnancy.